The Effect of Origami Play Therapy on the Social Skills of Children with Intellectual Disabilities - Selli Tria Amanda; Shulhan Arief Hidayat (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Children with intellectual disabilities are individuals with intelligence below average, generally have barriers to social skills. Therapy to improve children's social skills is by playing origami therapy. This study aims to determine the effect of origami play therapy on the level of social skills in children with intellectual disabilities.The study was conducted in February 2023. Experimental research design with one group pretest-posttest approach. The total population is 89 students. The sampling technique through purposive sampling obtained 30 samples, data analysis with the Wilcoxon test. The results of social skills research before therapy most respondents had less social skills as much as 19 (63.3%), while after therapy, social skills increased, namely more than half 13 (43.3%) respondents had good social skills. In the statistical test, the result is a ρ value of 0.000, meaning that there was an effect of origami play therapy on the level of social skills in children with intellectual disabilities at Special Education School C Tulungagung. Origami play therapy carried out in groups will cause social interaction between children and peers so that they can improve children's social skills. It is recommended for educators to implement scheduled play therapy so that children's social skills are better.